Part I: synthesis of benzoazetes by vinylic nucleophilic substitution reactions, Part II: synthesis of polycyclic arenes by copper-catalyzed cyclization of 2-alkenylphenyl ketones. - Tnay, Ya Lin. (2011)
Concerted nucleophilic substitution on an sp3 carbon has been one of the most useful reactions in organic chemistry. However, such concerted substitutions on unactivated vinyl carbons were thought to be impossible until recent experimental evidence. For example, the author’s group recently reported the cyclization of unactivated vinyl halides having an alcohol, sulfonamide, active methine, and thiol counterparts at suitable positions via concerted intramolecular vinylic substitution reaction. Such concerted intramolecular vinylic substitution also afforded a unique class of four–membered ring compounds, 2-alkylidenethietanes.